CompTIA IT Fundamentals ITF+ (FCO-U61) Exam Prep Course - Seminars, Total; Jernigan, Scott (Packt Publishing, 2020)
Learn how to effectively set up, configure, and secure IT devices independently About This Video Gain a solid understanding of PC and mobile software installation and configuration Develop the skills and confidence to pass the CompTIA ITF+ certification (FC0-U61) exam Learn how to safeguard local machines and networking devices In Detail Whether you are looking to pass the CompTIA IT Fundamentals (ITF+) certification (FC0-U61) exam or just want to impress your friends and colleagues with your exceptional IT skills, this course will help you to master IT fundamentals in a simple and engaging way. The course starts with the fundamentals of IT and takes you through the basics of computer components and networking. Next, you'll explore different operating systems, understand data storage and sharing, and work with file management tools. As you make progress, you'll explore the process of setting up and configuring basic computer workstations and mobile devices. After you've become familiar with the basics, you'll set up Wi-Fi devices and shared printers and explore options for achieving high-speed internet. You'll then discover techniques to identify and prevent basic security risks and solve compatibility issues. You'll also grasp troubleshooting and computer maintenance concepts and gain a clear understanding of basic database concepts and programming fundamentals. By the end of this course, you'll have become well-versed with IT fundamentals and developed the skills needed to pass the CompTIA ITF+ certification (FC0-U61) exam.
Keywords: Electronic videos